Predictors of use of dental care by children in north-central Appalachia in the USA. - Cecelia I Nelson (Public Library of Science (PLoS), 2021)
Use of dental services in childhood, especially preventive care, is associated with many important oral health outcomes throughout life. The Andersen behavioral model of healthcare utilization posits that predisposing characteristics, enabling resources, and need factors predict utilization in oral and other healthcare domains. Inequities that produce lower utilization of dental services in north-central Appalachia have been documented in comparison to the USA generally. Additionally, within Appalachia, there are disparities, such as those across different states related to varying public policies and resources supporting healthcare. Predictors of dental utilization in Appalachia have been a focus in adults, but less so in children. The aim of the current study was to understand predictors of dental utilization in children in north-central Appalachia in order to inform future research about how to intervene to address these disparities. In this study, there were 1,178 children, ages 1 through 10 years, from selected representative counties in West Virginia and Pennsylvania, along with a parent/caregiver, who were part of the Center for Oral Health Research in Appalachia (COHRA1) cohort. Use of dental services by their child was indicated by parents/caregivers, who also reported on sociodemographic, dental care-related anxiety and fear, and values and attitudes associated with oral healthcare. Results indicated that use of professional dental services by children was related to child age, dental anxiety and fear, and parental oral health values and attitudes. Older children in this age group, those who evidenced more dental care-related anxiety and fear, and whose parent/caregiver placed higher value on oral health and healthcare for themselves, were more likely to have had a dental visit in the past year.